Electroluminescent synaptic devices with logic functions. (December 2018) - Zhao, Shuangyi; Ni, Zhenyi; Tan, Hua; Wang, Yue; Jin, Hao; Nie, Tongxin; Xu, Mingsheng; Pi, Xiaodong; Yang, Deren
Abstract: The incorporation of light into synaptic devices for neuromorphic computing with low energy consumption and high intelligence is greatly inspired by the development of optogenetics in neuroscience. However, the use of light as the outputs of synaptic devices has not been demonstrated yet, impeding the full optoelectronic integration of artificial neural systems. Here we demonstrate electroluminescent synaptic devices based on silicon nanocrystals (Si NCs) with optical outputs. These devices exhibit a series of important synaptic functionalities including paired-pulse facilitation (PPF), transition from short-term plasticity (STP) to long-term plasticity (LTP) and spike-timing-dependent plasticity (STDP). In the meantime, logic functions such as "AND", "OR", "NAND" and "NOR" are realized in the intercoupled Si-NC-based electroluminescent synaptic devices. The current results not only help realize the bidirectional conversion between electrical and optical signals in synaptic devices, but also contribute to the development of the in-memory computing capacity of synaptic devices. Graphical abstract: Electroluminescent synaptic devices based on silicon nanocrystals (Si NCs) have been fabricated. Under the stimulation of electrical spikes these devices give out electroluminescence (EL) that decays in the timeframe of tens of microseconds, exhibiting a series of important synaptic functionalities and logic functions. Highlights: Electroluminescent synaptic devices are fabricated by using silicon nanocrystals (Si NCs). The electroluminescent synaptic devices with electrical inputs and optical outputs exhibit important synaptic functionalities. The logic functions of "AND", "OR", "NAND" and "NOR" can be realized by using the electroluminescent synaptic devices.